Transtorno do Espectro Autista: Atuação do Professor de Apoio Pedagógico no Ensino Fundamental - Prause, Vanessa Fernandez (2020)
The aim of this research is to understand how the Pedagogical Support Teacher (PST) organizes the teaching and the assistence to students with Autism Spectrum Disorder (ASD), who is starting in the first years of the Elementary School, according to the current legislation, in the municipal system education. It is also based on Cultural Historic Theory and is expressed as a qualitative research, which involved bibliographic analysis of academic productions from years 2009 to 2018, in the BDTD, CAPES and SCIELO databases, with a purpose to being a field research with observation, interview and questionnaire application. In Cascavel municipal public school system, in 2018, there were 62 schools and 71 students with Autism Spectrum Disorder enrolled in elementary school. For the data collection, two schools were selected in each region of the city (North, South, East, West and center) which had the largest number of students with ASD enrolled and with PST attendence. Twelve ASD students, fifteen PST and one municipal pedagogical coordenator were envolved in this research. The analysis focused on pedagogic work what envolved ASD students, showed that in 100 % of the cases there was adaptation of content and avaluation. 100% of the PST used pedagogical resources and faced them as very necessary resources. 47% participated in continuos training focused on ASD students. But the analysis of the speech of the teachers revealed in 73% of the PST presented a truncated language and without a fluency when they discribed their own work. These data were unexpected considering their age and their experience as regular education teachers. However, it was realized that 60% of these teachers had less than one year working in this area. This research concluded that work as PST requires to deny the common regular education and these teachers need to appropriate themselves to a different form of teaching, in the case of ASD students, it doesn´t have a preestablished single way of teaching, but that one supported by the teaching conception proposed by Historical Cultural Theory about how the students learn and understand, the teaching activities are the determining factor to get the knowledge. Beyond this factor, the PSTs need conditions to organize the teaching, they need continuos training, they need to access the content previously and they need availability of pedagogic resources and to dialogue with the conducting teacher, as well as, it needs to have a comprehension of the school team and the municipal pedagogical system, because the ASD development is not exclusive responsibility of the PST.